PENGARUH PEMAHAMAN WAJIB PAJAK, EFEKTIVITAS SISTEM PERPAJAKAN, KUALITAS PELAYANAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Tazaka, Asep Tsauriman; Friska, Yuliana (Publika Citra Media, 2025)
This research aims to determine and analyze to obtain empirical evidence of the influence of Taxpayer Understanding, Taxation System Effectiveness, and Taxation Service Quality on Taxpayer Compliance among Pamulang University Students majoring in Accounting Regular CS Semesters 6, 7, and 8. The Dependent Variable in this research is Taxpayer Compliance, while the Independent Variables in this research are Taxpayer Understanding, Taxation System Effectiveness, and Taxation Service Quality. This research is of a quantitative type and uses associative methods and data sourced from questionnaires distributed to research objects, namely Pamulang University students majoring in CS Regular Accounting, Semester 6, 7 and 8. Data analysis uses multiple linear regression analysis. Data processing uses SPSS software and the confidence level used is 5%. Based on the research results in the form of the Taxpayer Understanding variable, the t-count value was 2.077 > t-table 1.98350, indicating that Taxpayer Understanding has a significant effect on Taxpayer Compliance. The Tax System Effectiveness variable obtained a t-calculated value of 4.513 > t-table 1.98350, indicating that the Effectiveness of the Tax system has a significant effect on Taxpayer Compliance. The Tax Service Quality variable obtained a t-count value of 1.653 < t-table 1.98350, indicating that Tax Service Quality has no effect on Taxpayer Compliance.